Analysis of the evolution and variation of the human influenza A virus nucleoprotein gene from 1933 to 1990. - Shu, L L (1993)
This study examined the evolution and variation of the human influenza virus nucleoprotein gene from the earliest isolates to the present. Phylogenetic reconstruction of the most parsimonious evolutionary path connecting 49 nucleoprotein sequences yielded a single lineage. The average calculated rate of mutation was 3.6 nucleotide substitutions per year (2.3 x 10(-3) substitutions per site per year). Thirty-two percent of these mutations resulted in amino acid substitutions, and the remainder were silent mutations. Analysis of virus isolates from China and elsewhere showed no significant differences in their rate of evolution, genetic diversity, or mean survival time. The nearly constant rate of change was maintained through the two antigenic shifts, and there were no obvious changes in the number or types of mutations associated with the changes in the surface proteins. A detailed comparison of the changes that have occurred on the main evolutionary path with those that have occurred on the side branches of the phylogenetic tree was made. This showed that while 35% of the mutations on the side branches resulted in amino acid changes, only 21% of those on the main path affected the protein sequence. These results suggest that although the rate of change of the human influenza virus nucleoprotein is much higher than that previously described for avian influenza viruses, there are measurable constraints on the evolution of the surviving virus lineage. Comparison of the nucleoproteins of virus isolates adapted to chicken embryos with the nucleoproteins of those grown only in MDCK cells revealed no consistent differences between the virus pairs. Thus, although the nucleoprotein is known to be critical for host specificity, its adaptation to growth in eggs apparently involves no immediate selective pressures, such as are found with hemagglutinin.